THE IMPACT FROM FINANCIAL RATIOS ON ALTMAN Z-SCORES' MODEL TOWARDS STOCKS RETURN (STUDY IN AUTOMOTIVE SUBSECTORS COMPANIES AND ITS COMPONENTS THAT LISTED ON INDONESIA STOCK EXCHANGE) - Wirto, Wirto; H. Mustafa, Matrodji (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This research aims to revealed the affect from financial ratios to Altman Z-score model on stock returns in automotive sub-sector companies and its components that listed on the IDX. The research outcome shows in accordance with panel data regression results the WCTA variable on stock returns had a positive and significant affect, this could be cause of the large number of speculative investors who invest for long term so they could see the WCTA ratio for consideration in assessing the stock returns, the RETA variable on stock returns had a positive and significant affect, this could be cause of investors do not really considering the dividends or profits which distributed to larger shareholders so the investors would see the ratio of RETA when consideration the stock return appraisal, the EBITTA variable on stock returns had a positive and significant affect, this is because some investors see this ratio to revealed the company's ability to earned profits from assets before debt and tax payments because if the EBITTA ratio decrease, the stock return value would also decrease and it does conversely if EBITTA increase, the stock return value would increase. The MVEBTL variable on stock returns had a positive and significant affect because if the MVEBTL ratio decrease, meaning that there has an increase in the company's total debt and this ratio would illustrates the company's ability to fulfill its obligations from its own capital market value (common stock) and certainly this would be the one that would be the attention of investors before evaluating the stock returns.